Book Review of "Jungian Music Psychotherapy: When Psyche Sings" - Anderson, Kristen L. (Canadian Journal of Counselling and Psychotherapy, 2020)
Joel Kroeker’s book, Jungian Music Psychotherapy: When Psyche Sings, is a sophisticated presentation of the impact of sound and music in analytic depth psychology. It lays out a solid foundation for both music and analysis then bridges the two. The author introduces his archetypal music psychotherapy modality and translates the main analytical elements of Jungian technique into specific musical processes. For clinicians, educators, and those interested in the power of sound and music, this is a potent resource for understanding the relationship between sound, music, and musical imagery and their impact on our human psyche.